(untitled) (Jurnal Pustaka, 2025)
The stone jumping tradition, known as "hombo batu" in the Nias language, is an integral part of the cultural identity of the Nias people. This tradition continues to be preserved in the traditional village of Bawomataluo. This paper focuses on examining the historical development of hombo batu from its origins to the present day, particularly in relation to societal adaptation as a consequence of external and internal changes within the social system of the Nias community. Using a qualitative research method, data was collected from both secondary and primary sources, including literature reviews, observations, and interviews. The gathered data was systematically compiled and analyzed. The theoretical analysis employs a functionalist perspective, examining both latent and manifest functions, as well as concepts of tradition, social change, and cultural adaptation in the modern era. Despite its evolving functions, hombo batu maintains a sense of continuity and stability within Nias society. The tradition has undergone a functional transformation—from its original role as a form of military training and victory ritual to its contemporary function as a tourist attraction and cultural symbol. A key latent function of preserving hombo batu lies in its ability to safeguard the cultural identity of the Nias people while reinforcing social cohesion, serving as a distinctive marker of identity for both individuals and the broader Nias community.